2001
DOI: 10.1093/jn/131.12.3243
|View full text |Cite
|
Sign up to set email alerts
|

Various Indigestible Saccharides Enhance Net Calcium Transport from the Epithelium of the Small and Large Intestine of Rats In Vitro

Abstract: An Ussing chamber technique was used to determine the effects of six indigestible saccharides on net Ca absorption from the luminal side to the basolateral side of isolated preparations of rat jejunal, ileal, cecal and colonic epithelium in vitro. The concentrations of Ca in the Tris buffer solution on the serosal side and on the mucosal side were 1.25 and 10 mmol/L, respectively. After a 30-min incubation, the Ca concentration in the serosal medium was determined and the net transepithelial Ca transport was c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
59
0
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(65 citation statements)
references
References 24 publications
5
59
0
1
Order By: Relevance
“…In an in vitro study, fructooligosaccharides increased the net transport of Ca in the small and large intestines of rats (Mineo et al 2001). Kruger et al (2003) reported that the effects of fructooligosaccharides with various degree of polymerization (DP) on Ca bioavailability and bone mineralization in rats were not the same.…”
Section: Resultsmentioning
confidence: 99%
“…In an in vitro study, fructooligosaccharides increased the net transport of Ca in the small and large intestines of rats (Mineo et al 2001). Kruger et al (2003) reported that the effects of fructooligosaccharides with various degree of polymerization (DP) on Ca bioavailability and bone mineralization in rats were not the same.…”
Section: Resultsmentioning
confidence: 99%
“…NMR spectra were recorded at room temperature with a Bruker AMX 500 spectrometer ( 1 H 500 MHz, 13 C 125 MHz) equipped with a 5 mm diameter C H dual (1D spectra) and TXI probe (2D spectra). Chemical shifts of 1 H (δH) and 13 C (δC) in ppm were determined relative to the external standard of sodium [2,2,3,3 2 H4] 3 (trimethylsilyl)propanoate in D2O (δH 0.00 ppm) and 1,4 dioxane (δC 67.40 ppm) in D2O, respectively.…”
Section: Gas Liquid Chromatography (Gc)mentioning
confidence: 99%
“…They are classified into homooligosaccharides such as xylooligosaccharide, maltooligosaccharide and inulooligosaccharide, and heterooligosaccharides such as fructooligosaccharide, galactooligosaccharide, soybeenoligosaccharide, raffinose and palatinose. Thus, they are thought to selectively increase bifidobacteria, 1) enhance immune responses, 2) promote the absorption of minerals, 3) and more recently, prevent diseases such as a heart diseases, hypertension, diabetes and osteoporosis.…”
mentioning
confidence: 99%
“…It has been suggested that the mechanistic action of stimulated calcium absorption by resistant sugars is passive, involving an increase in perfused fluid within the lumen to maintain isotonicity and consequently an increase in permeability of the intracellular junctions between enterocytes (Brommage et al, 1993). Alternatively, in vitro sugar-induced changes in the transepithelial permeability of the intestinal epithelium via the activation of tight junctions have also been suggested (Mineo et al, 2001).…”
Section: Discussionmentioning
confidence: 99%